Outcomes of 3, 737 COVID-19 patients treated with hydroxychloroquine/azithromycin and other regimens in Marseille, France: A retrospective analysis. Issue 36 (July 2020) - Lagier, Jean-Christophe; Million, Matthieu; Gautret, Philippe; Colson, Philippe; Cortaredona, Sébastien; Giraud-Gatineau, Audrey; Honoré, Stéphane; Gaubert, Jean-Yves; Fournier, Pierre-Edouard; Tissot-Dupont, Hervé; Chabrière, Eric; Stein, Andreas; et al.
Abstract: Background: In our institute in Marseille, France, we initiated early and massive screening for coronavirus disease 2019 (COVID-19). Hospitalization and early treatment with hydroxychloroquine and azithromycin (HCQ-AZ) was proposed for the positive cases. Methods: We retrospectively report the clinical management of 3, 737 screened patients, including 3, 119 (83.5%) treated with HCQ-AZ (200 mg of oral HCQ, three times daily for ten days and 500 mg of oral AZ on day 1 followed by 250 mg daily for the next four days, respectively) for at least three days and 618 (16.5%) patients treated with other regimen ("others"). Outcomes were death, transfer to the intensive care unit (ICU), ≥10 days of hospitalization and viral shedding. Results: The patients' mean age was 45 (sd 17) years, 45% were male, and the case fatality rate was 0.9%. We performed 2, 065 low-dose computed tomography (CT) scans highlighting lung lesions in 592 of the 991 (59.7%) patients with minimal clinical symptoms (NEWS score = 0). A discrepancy between spontaneous dyspnoea, hypoxemia and lung lesions was observed. Clinical factors (age, comorbidities, NEWS-2 score), biological factors (lymphocytopenia; eosinopenia; decrease in blood zinc; and increase in D-dimers, lactate dehydrogenase, creatinine phosphokinase, troponin and C-reactive protein) and moderate and severe lesions detected in low-dose CT scans were associated with poor clinical outcome. Treatment with HCQ-AZ was associated with a decreased risk of transfer to ICU or death (Hazard ratio (HR) 0.18 0.11–0.27), decreased risk of hospitalization ≥10 days (odds ratios 95% CI 0.38 0.27–0.54) and shorter duration of viral shedding (time to negative PCR: HR 1.29 1.17–1.42). QTc prolongation (>60 ms) was observed in 25 patients (0.67%) leading to the cessation of treatment in 12 cases including 3 cases with QTc> 500 ms. No cases of torsade de pointe or sudden death were observed. Conclusion: Although this is a retrospective analysis, results suggest that early diagnosis, early isolation and early treatment of COVID-19 patients, with at least 3 days of HCQ-AZ lead to a significantly better clinical outcome and a faster viral load reduction than other treatments.